Meira Paibis Movement Roles in Creating Peace at Northeastern India - Derina Faslig Silitonga (Jurnal Hubungan Internasional, 2021)
Starting from the aim of stopping the rebel movement, the enactment of the Armed Forces Special Powers Act (AFSPA) of 1958 in practice became a boomerang for security stability in Northeastern India. The privileges granted by the government to soldiers are used as a pretext for discrimination and violations of human rights. The patriarchal tradition, which then considers women as property and weak creatures, causes women and children to suffer the most. Reports of sexual harassment cases, rape, and even murder unilaterally encouraged Meira Paibis as a grassroots women's movement to develop a strategy of resistance. Meira Paibis uses a non-violent approach through symbolic methods that are viewed as extreme and controversial in its mission. This research will describe the significant role of the Meira Paibis women's movement in organizing resistance to AFSPA policies and their efforts to achieve positive peace in Northeastern India. This paper will elaborate on the non-violence approach to see the strategies played by Meira Paibis and the obstacles faced in the process of achieving her goals.